(3GdJYHjQ GdbGOQi aj JaSjQ GdCMdGes - (3fUQ Hf jYbhH Hf EHQGgje GdOjfhQj, CHh SYO,J (B410 (3g` s
(3ChdgG (B:s
(3GdeMehO Gddg dG Edg EdG gh GdMi Gdbjhe dG JCNPg SfI hdG fhe s
(3BNQgG (B:s
(3CeG GdghOL agh GdeQCI dCfg ef eQcH GdfSGA hGddg CYde hjJdhg ai GdLRA G dKGfi GdaUd GdQGHY YTQ s
(3Cda gPG GdcJGH ddNdjaI CHh GdYHGS dGbGOQ HGddg hLYdg ai KdGKjf aUdkG JMJ cd aUd CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B29s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3JYHjQ GdQDjGs